Unraveling the structure and composition of Varadero Reef, an improbable and imperiled coral reef in the Colombian Caribbean - Pizarro, Valeria (PeerJ, 2017)
Coral reefs are commonly associated with oligotrophic, well-illuminated waters. In 2013, a healthy coral reef was discovered in one of the least expected places within the Colombian Caribbean: at the entrance of Cartagena Bay, a highly-polluted system that receives industrial and sewage waste, as well as high sediment and freshwater loads from an outlet of the Magdalena River (the longest and most populated river basin in Colombia). Here we provide the first characterization of Varadero Reef’s geomorphology and biological diversity. We also compare these characteristics with those of a nearby reference reef, Barú Reef, located in an area much less influenced by the described polluted system. Below the murky waters, we found high coral cover of 45.1% (±3.9; up to 80% in some sectors), high species diversity, including 42 species of scleractinian coral, 38 of sponge, three of lobster, and eight of sea urchin; a fish community composed of 61 species belonging to 24 families, and the typical zonation of a Caribbean fringing reef. All attributes found correspond to a reef that, according to current standards should be considered in “good condition”. Current plans to dredge part of Varadero threaten the survival of this reef. There is, therefore, an urgent need to describe the location and characteristics of Varadero as a first step towards gaining acknowledgement of its existence and garnering inherent legal and environmental protections.